Effectiveness and safety of injectable human papilloma virus vaccine administered as eyedrops. Issue 1 (4th January 2023) - Kim, Jiyeon; Kim, Eun-Do; Shin, Hae-Sol; Han, Soo Jung; Jamiyansharav, Munkhdelger; Yoon, Sang Chul; Lee, Jihei Sara; Seo, Kyoung Yul
Abstract: Mucosal vaccines have the advantages of ease of administration and the induction of strong mucosal immunity and a systemic immune response. Recently, the eye mucosa has been shown to be an effective and safe alternative vaccination route against influenza, Toxoplasma gondii infection, and hemolytic uremic syndrome in mice. In this study, we showed that the commercially available human papilloma virus (HPV) vaccine, Cervarix, induced significant immune reactions in terms of anti-HPV antigen (Ag)-specific immunoglobulin G (IgG) and IgA antibody production following eyedrop (ED) vaccination in mice. The HPV ED vaccines (EDV) provoked no signs of inflammation within 24 h, as indicated by the inflammatory cytokine mRNA levels and infiltration of mononuclear cells in inoculation sites. Moreover, the morphology of the cornea and retina and intraocular pressure of mice did not change after the HPV EDV. The functions of photoreceptor cells, including rod and cone cells, were normal following the HPV EDV inoculation in mice. These results suggest that Cervarix EDV could be a potent, safe, and effective mucosal vaccine against HPV-associated cancers.